The Analisis Social Ecology System-Action Situation untuk Kerangka Kerja Memulihkan Bumi: Sebuah Proposal Aplikatif Artikel 138 Ensiklik Laudato Si’ - Alexander Aur (Sapientia Humana: Jurnal Sosial Humaniora, 2021)
Pope Francis issued the Encyclical Laudato Si' on May 24, 2015. Based on the results of scientific research on various environmental problems in various parts of the world, the Pope appealed to Catholics around the world to restore the earth from human actions that destroy nature. Restoring the earth as a common home. This encyclical received a wide response from various circles. Various parties pay attention to this encyclical. This article is a response to the encyclical. In this paper, the author will analyzes article 138, which in this encyclical is in Chapter IV entitled “Integral Ecology”. To analyze the article, the author uses, first, a social ecology system-action situation (SES-AS) approach as an analytical method. Second, several models approach nature as a theoretical framework for deepening integral ecology. Thus, Laudato Si' obtains an applied and theoretical framework. Applicable framework for concrete action. Theoretical framework for reflection on concrete action.